The AI Revolution in Healthcare: Predictions for 2030 - Rasit, Dinc (Rasit Dinc Digital Health & AI Research, 2024)
The integration of Artificial Intelligence AI into healthcare is not a distant prospect but a rapidly accelerating reality. As we approach 2030, AI is poised...
Keywords: Drug Discovery; Digital Health; Diagnostics; Artificial Intelligence; Healthcare Innovation